2016
DOI: 10.1186/s13071-016-1500-y
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Schistosoma mansoni infection using a Fasciola hepatica-derived fatty acid binding protein from different delivery systems

Abstract: BackgroundSchistosomiasis is a water-borne disease afflicting over 261 million people in many areas of the developing countries with high morbidity and mortality. The control relies mainly on treatment with praziquantel. Fatty acid binding proteins (FABP) have demonstrated high levels of immune-protection against trematode infections. This study reports the immunoprotection induced by cross-reacting Fasciola hepatica FABP, native (nFh12) and recombinantly expressed using two different expression systems Escher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…The first injection contains AA0029 and Qs emulsified in Montanide, and the second injection, administered 5 days after the first, contains the antigen with AA0029 and Qs in the emulsion oil. Individual doses per injection in mice included 100 μg of AA0029, 20 μg of Qs, and 10 μg of either SmKT or SmKB in a final 100-μl volume of emulsion with Montanide based on our prior experience (54, 55). Mice were weighed and monitored for signs of anaphylactic shock, erythema at the injection site, and changes in behavior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first injection contains AA0029 and Qs emulsified in Montanide, and the second injection, administered 5 days after the first, contains the antigen with AA0029 and Qs in the emulsion oil. Individual doses per injection in mice included 100 μg of AA0029, 20 μg of Qs, and 10 μg of either SmKT or SmKB in a final 100-μl volume of emulsion with Montanide based on our prior experience (54, 55). Mice were weighed and monitored for signs of anaphylactic shock, erythema at the injection site, and changes in behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were weighed and monitored for signs of anaphylactic shock, erythema at the injection site, and changes in behavior. Vaccinated and infection control mice were percutaneously challenged with 150 ± 8 S. mansoni cercariae by the ring method 2 weeks after the third vaccination (5355). Mice were restrained with a mixture of 50 mg/kg ketamine (Imalgene1000, Merial), 5 mg/kg diazepam (Valium10, Roche Farma SA), and 1 mg/kg atropine (B. Braun, Madrid) administered intraperitoneally.…”
Section: Methodsmentioning
confidence: 99%
“…For intestinal schistosomiasis, a recombinant S. mansoni 14 kDa monovalent fatty acid-binding protein (Sm14) (Moser et al, 1991 ; Tendler and Simpson, 2008 ; Coler et al, 2011 ), is currently in the final stages of phase II field trial testing in adult male subjects from endemic regions in Africa and Brazil (Supplementary Table 1 ) (Ricciardi and Ndao, 2015 ; Tendler et al, 2015 ; Santini-Oliveira et al, 2016 ). This antigen also shows promise as a dual-purpose helminthic vaccine against veterinary fasciolosis by conferring complete protection in mice challenged with Fasciola hepatica (67% for S. mansoni ) (Tendler et al, 1996 ) and vice versa with a similar native protein isolated from Fasciola hepatica (nFh12) that cross-protected mice against S. mansoni infection (>80% efficacy) (Vicente et al, 2016 ). This study is currently active and promising results could eventually lead to the first human antihelmintic vaccine.…”
Section: Endoparasite Vaccines: Helminthiasesmentioning
confidence: 99%
“…Accordingly, previous studies have shown that the FABP, which absorbs, transports, and transforms fatty acids in host cell membranes (2), comprises a single effective vaccine against at least two parasites, Fasciola hepatica and S. mansoni (3). Furthermore, the FABP derived from F. hepatica has been reported to exert a strong protective effect against S. mansoni infection (4), and similarly, a recombinant S. mansoni FABP-pcDNAI plasmid was previously reported to elicit a high level of sm FABP-IgG antibody production, and to cause a strong (74.2%) decrease in the number of adult worms, as well as the number of eggs and granulomas (5). Moreover, the specific immune response elicited by, and tolerance of male volunteers (in non-schistosomiasis endemic areas) for a Sm FABP vaccine (formulated with a glucopyranosyl lipid A adjuvant, in an oil-in-water emulsion) has been successfully analyzed via landmark, open-knowledge phase-I and IIa clinical trials (6), and is currently being evaluated by phase-II/III trials (7).…”
Section: Introductionmentioning
confidence: 99%